Hydrophobic perfluoroalkane modified metal‐organic frameworks for the enhanced electrocatalytic reduction of CO2. Issue 1 (25th January 2022) - Yang, Xu; Li, Qiu‐Xia; Chi, Shao‐Yi; Li, Hong‐Fang; Huang, Yuan‐Biao; Cao, Rong
Abstract: The electrochemical reduction of CO2 to value‐added chemicals would be an efficient way to utilize CO2 and mitigate greenhouse gas emission. However, the associated competitive hydrogen evolution reaction (HER) in aqueous electrolytes usually leads to poor selectivity for the CO2 electroreduction reactions (CO2 RR). Due to their high specific surface areas and tunable single active sites, metal‐organic frameworks (MOFs) are considered as promising candidates for CO2 RR. Herein, the Fe‐porphyrin based Zr‐MOF, PCN‐222(Fe), was treated with perfluorocarboxylic acid to afford the hydrophobic F n ‐PCN‐222(Fe) ( n  = 5 and 7, n is the number of fluorine atoms in the perfluoroalkyl chain) for improving the selectivity CO2 RR via inhibiting the HER. Owing to the single active Fe sites were positioned in a hydrophobic microenvironment, the optimal F5 ‐PCN‐222(Fe) shows a high Faradic efficiency of 97% toward production of CO at −0.7 V versus reversible hydrogen electrode. Meanwhile, F5 ‐PCN‐222(Fe) achieved a high turnover frequency value of 3850 h −1 at −0.8 V, which was almost 3.6 times higher than that of PCN‐222(Fe) and surpassed most of other reported MOFs. This study paves a new way to improve the selectivity of the CO2 RR via inhibiting the associated HER by increasing the hydrophobicity of the electrocatalysts. Abstract : The local environment of active centers plays a vital role in the CO2 electroreduction reactions (CO2 RR). Hydrophobic metal‐organic framework, F n ‐PCN‐222(Fe), were prepared by post‐modification of perfluoroalkyl chains and used for CO2 RR. Compared with the pristine PCN‐222(Fe), the CO faradic efficiency of F n ‐PCN‐222(Fe) is significantly improved.